Neuroprotective Effect of Fisetin Through Suppression of IL-1R/TLR Axis and Apoptosis in Pentylenetetrazole-Induced Kindling in Mice - Khatoon, Saima; Agarwal, Nidhi Bharal; Samim, Mohammed; Alam, Ozair (Frontiers in Neurology, 2021)
Epilepsy is a complex neurological disorder, characterized by frequent electrical activity in the brain regions. Inflammation and apoptosis cascade activation are serious neurological sequelae during seizures. Fisetin (3, 3′,4′,7-tetrahydroxyflavone), a flavonoid molecule, is considered for its effective anti-inflammatory and anti-apoptotic properties. The present study investigated the neuroprotective effect of fisetin in experimental epilepsy. For acute studies, increasing current electroshock (ICES) and pentylenetetrazole (PTZ)-induced seizure tests were used to evaluate antiseizure activity of fisetin. For chronic study, kindling model was established by intraperitoneal (i.p.) administration of subconvulsive dose (25 mg/kg) of PTZ. Mice were treated with fisetin (5, 10 and 20 mg/kg) to study its probable antiseizure mechanism. The kindled mice were evaluated for seizure scores, neuronal damage, inflammatory and apoptotic markers. Histological alterations were observed in hippocampus of experimental mice. Levels of high mobility group box 1 (HMGB1), toll like receptor-4 (TLR-4), interleukin-1 receptor 1 (IL-1R1), interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) were assessed in brain tissues using ELISA. The immunoreactivity and mRNA expressions of nuclear factor- κB (NF-κB), cyclooxygenase-2 (COX-2), cytochrome C and caspase-3 were quantified by immunohistochemical analysis and real-time PCR. Phosphorylation ELISA was used to evaluate AkT/mTOR (mammalian target of rapamycin) activation in brain regions of kindled mice. Our results showed that fisetin treatment increased the seizure threshold current (STC) in ICES test. In PTZ-induced seizures, fisetin administration increased the latency for myoclonic jerks (MJ) and generalized seizures (GS). In PTZ-induced kindling, fisetin treatment attenuated seizure activity and the associated neuronal damage in experimental mice. Also, fisetin treatment ameliorated kindling-induced neuroinflammation evident from decreased levels of HMGB1, TLR-4, IL-1R1, IL-1β, IL-6 and TNF-α in the brain tissues of kindled mice. Also, the immunoreactivity and mRNA expressions of inflammatory molecules, NF-κB and COX-2 were decreased with fisetin administration in kindled animals. Decreased phosphorylation of Akt/mTOR pathway was reported with fisetin treatment in hippocampus and cortex of kindled mice. The immunoreactivity and mRNA expressions of apoptotic molecules, cytochrome C and caspase-3 were attenuated upon fisetin administration. The findings suggest that fisetin has neuroprotective effect by suppressing release of inflammatory and apoptosis molecules and attenuating histological alterations.